Geriatric chest disease - Harris, Luke, M.B (J. Wright, 1974)
Geriatric Chest Disease presents a guide to the management of chest disease in the elderly. It discusses the treatment and multiple pathology of the said disease. It addresses the normal changes in the aging lung. Some of the topics covered in the book are the symptoms of dyspnoea; cough; haemoptysis; the physical signs of diffuse airways obstruction; bronchography; bronchial carcinoma; the pneumonias; pulmonary tuberculosis; pulmonary thrombo-embolic disease; pleural effusion; fungal infection; and systemic lupus erythematosus. The symptomatic management of fractured ribs and hiatus hernia ar.